2019
DOI: 10.1371/journal.pone.0217869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antimicrobial nanocomposites on Vibrio cholerae lifestyles: Pellicle biofilm, planktonic and surface-attached biofilm

Abstract: Vibrio cholerae is an important human pathogen causing intestinal disease with a high incidence in developing countries. V. cholerae can switch between planktonic and biofilm lifestyles. Biofilm formation is determinant for transmission, virulence and antibiotic resistance. Due to the enhanced antibiotic resistance observed by bacterial pathogens, antimicrobial nanomaterials have been used to combat infections by stopping bacterial growth and preventing biofilm formation. In this study, the effect of the nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
1
10
0
2
Order By: Relevance
“…25 This growth mode enhances environmental persistence, provides protection against a number of environmental stresses, and increases antibiotic resistance in MDR V. cholerae strains. 26 When V. cholerae strains enter the body, they must be physically protected against the acidic environment of the stomach. Biofilm network provides resistance to high acidity of the stomach environment.…”
Section: Discussionmentioning
confidence: 99%
“…25 This growth mode enhances environmental persistence, provides protection against a number of environmental stresses, and increases antibiotic resistance in MDR V. cholerae strains. 26 When V. cholerae strains enter the body, they must be physically protected against the acidic environment of the stomach. Biofilm network provides resistance to high acidity of the stomach environment.…”
Section: Discussionmentioning
confidence: 99%
“…Estamos empezando a reconocer los talentos de estos protagonistas; es decir, tanto su vasta diversidad, como el papel que desempeñan los microbios involucrados, lo cual tendrá implicaciones en nuestra vida futura, ya que el "éxito" de los biofilms influye en los mecanismos de salud-enfermedad de organismos y ecosistemas. De hecho, hoy sabemos que las infecciones en nuestro cuerpo están directamente vinculadas con el desarrollo de biopelículas (Meza-Villezcas et al, 2019). Además, pueden esconder claves para futuros desarrollos tecnológicos.…”
Section: ¿Has Visto Esta Película?unclassified
“…Hoy en día la biopelículas se usan para diversos procesos como el tratamiento de aguas residuales(González-Brambila et al, 2008) o la producción de biocombustibles(Ozkan et al, 2012). Los biofilms también son un factor clave en los mecanismos de salud-enfermedad, por lo que entender sus impactos nos llevará a rediseñar los tratamientos médicos, ya que anteriormente éstos se basaban en contener a un solo microorganismo patógeno(Morones Ramírez, 2009;Meza-Villezcas et al, 2019; uaeh 2019). Pero no te asustes demasiado: no todo lo que tenga que ver con microbios es malo.…”
unclassified
“…Vibrio cholerae is a pathogenic bacteria predominantly found in aquatic environments and capable of forming resilient biofilms displaying higher infectivity than planktonic bacteria. The effect of silver-based nanocomposites was recently evaluated against V. cholerae planktonic cells, surface-attached and pellicle biofilms, and the results showed that the susceptibility to these antimicrobials was highly dependent on the bacteria lifestyle . However, the role of V.…”
Section: Introductionmentioning
confidence: 99%
“…26−28 The effect of silver-based nanocomposites was recently evaluated against V. cholerae planktonic cells, surfaceattached and pellicle biofilms, and the results showed that the susceptibility to these antimicrobials was highly dependent on the bacteria lifestyle. 29 However, the role of V. cholerae EPS on susceptibility to AgNPs and the interactions between nanoparticles and the biofilm matrix have not been investigated yet.…”
Section: ■ Introductionmentioning
confidence: 99%